The mechanism underlying the functionalisation of cobalt nanoparticles by carboxylic acids: a first-principles computational study. Issue 24 (8th June 2021) - Farkaš, Barbara; Terranova, Umberto; de Leeuw, Nora H.
Abstract : Ab initio methods resolve mechanism behind carboxylic acid functionalisation of cobalt nanoparticles and identify the fate of dissociated hydrogen atoms. Abstract : The promise of biocompatible magnetic nanoparticles with high magnetic saturation in the implementation as drug carriers and hyperthermia agents has generated significant interest in functionalised cobalt nanoparticles. Carboxylic acid coatings on metallic nanoparticles have been shown as an attractive option owing to their respectable stability and biocompatibility. However, only limited information is available on the molecular mechanism leading to the formation of such protective coatings. In this study, ab initio molecular dynamics simulations have been used to unravel the functionalisation mechanism starting from a neutral cobalt cluster and valeric acid molecules. Three stages were detected in the coating process: (i) rapid initial adsorption of acid molecules, (ii) simultaneous adsorption of new molecules and dissociation of those already interacting with the cluster, and, finally, (iii) grouping of dissociated hydrogen atoms and subsequent desorption of acid molecules. The fate of the hydrogen atoms was probed through a combination of static and dynamic ab initio modelling approaches, which predicted H2 generation with favourable energetics. A better understanding of the functionalisation and interaction mechanisms will aid the rational design of biocompatible cobalt nanoparticles for various applications.